Pengaruh Iklim Psikologis Terhadap Keinginan Karyawan Untuk Keluar Perusahaan Melalui Kepuasan Kerja (Studi pada PT. Hervitama Indonesia) - Sukma Dewi, Esa Ayu; Kistyanto, Anang (Fakultas Ekonomi dan Bisnis, UNTAN, 2019)
PT. Hervitama Indonesia which is engaged in providing instrumentation goods and installation services has a work area for electrical installation, instrumentation, construction, interior and calibration works. Service provider in the field of electrical installation by PT. Hervitama Indonesia includes the strong and weak currents installation. The purpose of this study is to test and analyze the influence of psychological climate on the desires of employees to leave the company through job satisfaction for employees of PT. Hervitama Indonesia. This research is a causality study with a quantitative approach. The sampling technique uses saturated samples with a total of 50 respondents to employees of PT. Hervitama Indonesia. The statistical analysis used in this study was PLS with the help of smartPLS 3.0 software. The results of this study explain that the psychological climate has a negative and significant effect on the desire of employees to leave the company. Psychological climate has a positive and significant effect on job satisfaction. Job satisfaction does not affect the desire of employees to leave the company. The research implications that can be applied to companies, namely the need for leaders to improve the quality and quantity in terms of support provided to employees or subordinates can be done by way of guidance to employees in doing good work. For example, holding back inter-unit counseling that discusses the constraints of work in the field related to work.